A prospective randomized controlled trial comparing two different treatments of intrauterine adhesions. Issue 6 (June 2020) - Huang, Xiao-Wan; Lin, Meng-Meng; Zhao, Hong-Qin; Powell, Martin; Wang, Yuan-Qiu; Zheng, Ru-Ru; Ellis, Laura Burney; Xia, Wei-Ting; Lin, Feng
Abstract: Research question: Intrauterine adhesions (IUA) are primarily caused by trauma to the endometrium, and hysteroscopy is presently the main treatment for IUA. However, high rates of post-operative adhesion re-formation remain a problem. In this study, the combination of an intrauterine device (IUD) with a Foley catheter and the balloon uterine stent were investigated to evaluate their efficacy in preventing adhesion re-formation and the subsequent reproductive outcomes in patients with moderate to severe adhesions. Design: A prospective randomized controlled study was conducted in a university-affiliated hospital. A total of 171 women with Asherman's syndrome were initially recruited between August 2016 and December 2017 and were randomized to undergo either balloon uterine stent insertion or placement of a contraceptive IUD plus a Foley catheter after hysteroscopic adhesiolysis. Reduction of adhesion scores, incidence of adhesion re-formation, changes in menstrual flow and reproductive outcomes were analysed. Results: A total of 118 participants were eligible for analysis. The American Fertility Society (AFS) scores were not significantly different between groups before hysteroscopic adhesiolysis. At the second-look hysteroscopy, the AFS scores and adhesion recurrence rates were significantly higher in the balloon uterine stent group compared with the combination group ( P < 0.01 and P = 0.024, respectively). There were no statistically significant differences in pregnancy and live birth rates between the two groups. Conclusions: The combination of an IUD and a Foley balloon catheter had better efficacy in preventing adhesion re-formation than the balloon uterine stent alone; however, it did not produce better reproductive outcomes.